2021
DOI: 10.1007/s10734-021-00744-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-biased evaluation or actual differences? Fairness in the evaluation of faculty teaching

Abstract: How do we know if a faculty teaching evaluation is biased? Biasing factors studies are an influential source of evidence for arguing about biased teaching evaluations. These studies examine existing evaluation data and compare the results by gender, race, or ethnicity, interpreting a significant difference between subgroups as evidence of bias. However, only a difference explained by irrelevant aspects embedded in the evaluation would compromise its fairness. The study aims to amend how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…The largest group negatively impacted in SET results is almost universally accepted to be women, with many studies finding that women are disadvantaged by a statistically significant amount (Adams et al, 2021;Valencia, 2021). Boring et al (2016) found that higher performing women academics were often graded harsher in SETs to such an extent that they were placed in lower grading brackets (excellent, very good, good etc.)…”
Section: The Impact Of Set Results Prejudices and Biasmentioning
confidence: 99%
“…The largest group negatively impacted in SET results is almost universally accepted to be women, with many studies finding that women are disadvantaged by a statistically significant amount (Adams et al, 2021;Valencia, 2021). Boring et al (2016) found that higher performing women academics were often graded harsher in SETs to such an extent that they were placed in lower grading brackets (excellent, very good, good etc.)…”
Section: The Impact Of Set Results Prejudices and Biasmentioning
confidence: 99%
“…School education administrators or teachers may evaluate the teaching quality of courses according to the evaluation score. However, in the evaluation process, attention should be paid to the issue of fairness to avoid the interference of subjective factors of teachers and students (30).…”
Section: The Index Can Be Effectively Used To Evaluate Teaching Qualitymentioning
confidence: 99%
“…Students may have biases in their assessment depending on whether they are female or male when evaluating the performance of their teachers, in which the female teacher has also been more affected (Potvin and Hazari, 2016;Heffernan, 2021;Kreitzer and Sweet-Cushman, 2021). According to Valencia (2021), this situation may encourage students to accept and reproduce these gender biases in other social contexts. However, Kreitzer and Sweet-Cushman (2021) point out that the effect of student gender on teaching evaluation is conditioned to other factors.…”
Section: Differences Among Groupsmentioning
confidence: 99%
“…To date, little is known about possible differences according to the age of the student body in the appraisal of teaching in the context of University education, but differences in students' appraisal of teaching according to their level of advancement in their studies have been reported (Marsh and Hocevar, 1984;Kamran et al, 2012;Kalender, 2015;Müller et al, 2017;Kitto et al, 2019;Mocanu et al, 2021;Pérez-Villalobos et al, 2021). Similarly, differences have been reported according to the gender of the student body, with respect to the students' assessment of teaching and the performance of their teachers, in the context of higher education (Boring, 2015;Boring et al, 2016;Potvin and Hazari, 2016;Eouanzoui and Jones, 2017;Heffernan, 2021;Kreitzer and Sweet-Cushman, 2021;Valencia, 2021).…”
Section: Introductionmentioning
confidence: 99%